Enhancing physical activity promotion in midlife women with technology-based self-monitoring and social connectivity: A pilot study. (August 2016) - Butryn, Meghan L; Arigo, Danielle; Raggio, Greer A; Colasanti, Marie; Forman, Evan M
This pilot study tested a novel program to promote adoption and maintenance of aerobic activity in midlife women. Lifestyle modification group sessions were held weekly for 3 months, followed by two booster sessions during the 3-month maintenance phase. During all 6 months of the program, participants used a physical activity sensor to automate self-monitoring and a web platform to facilitate social connectivity. Aerobic exercise increased from 63 to 132 minute/week from baseline to 3 months ( p < .01), and activity was maintained at 6 months (135 minute/week). Technology enhancements have strong potential to promote maintenance of behavior change.